Water quality in individual groundwater supply systems in Southern Brazil - Schneider, Silvana Isabel; Golombieski, Jaqueline Ineu; Seben, Debora; Menegazzo, Kananda Cabral; Wastowski, Arci Dirceu; Borba, Willian Fernando de; Decezaro, Samara Terezinha; Medeiros, Raphael Corrêa (Ciência e Natura, 2021)
This study aimed to evaluate the potability of drinking water in ten municipalities of Rio Grande do Sul State, Brazil, distributed in rural and urban areas, with three different sources: springs, shallow wells, and deep wells. The water quality parameters analyzed from 2017 to 2019 were: pH, temperature, apparent and true color, turbidity, electrical conductivity, total alkalinity, total hardness, nitrate, total phosphorus, total iron, fluoride, biochemical oxygen demand, total coliforms, and Escherichia coli. A macroscopic analysis was also conducted in the surrounding of sampling points. According to the Brazilian and the WHO (World Health Organization) guidelines, some of the analyzed variables, in some sampling points, were in disagreement with the current both guidelines, which are pH, apparent color, turbidity, total iron, total coliforms, and Escherichia coli. The surveillance showed that the deeper the water is abstracted the less are natural and anthropogenic interferences in physical, chemical, and microbiological characteristics of the water; and the protection of the location where the water is abstracted improves its quality. Nonetheless, for the sampled waters it is necessary a disinfection process for posterior human consumption.